Rhnull phenotype caused by a novel RHAG mutation, c.945+1G>A, in the Japanese population. Issue 8 (16th April 2019) - Ushiki, Takashi; Tsuneyama, Hatsue; Masuko, Masayoshi; Kozakai, Takashi; Kasami, Takuya; Tanaka, Tomoyuki; Uchikawa, Makoto; Kitajima, Toshiki; Kasai, Emiko; Komata, Tae; Katagiri, Takayuki; Kamimura, Masami; et al.
Abstract : BACKGROUND: The Rh complex contributes to cell membrane structural integrity of erythrocytes. Rhnull syndrome is characterized by the absence of the Rh antigen on the erythrocyte membrane, resulting in chronic hemolytic anemia. We recently came across 3 Rhnull phenotype probands within two families with the same novel RHAG mutation in the Japanese population. MATERIALS AND METHODS: Detailed Rh phenotyping by hemagglutination was performed using monoclonal and polyclonal anti‐D, ‐C, −c, −E, and ‐e; monoclonal and polyclonal anti‐Rh17 antibodies; and polyclonal anti‐Rh29 antibodies. RHAG mRNA transcripts were analyzed by reverse transcription–polymerase chain reaction, and the mutation was verified by genomic sequencing. RESULTS: The genomic region spanning exon 6 contained a G > A transition in the invariant GT motif of the 5′ donor splice‐site of Intron 6 (c.945+ 1G> A). The Rhnull phenotype was caused by an autosomal recessive mutation in Probands 1 and 2, determined by family history. Regarding clinical features, the degree of hemolysis varied slightly between these individuals, with Proband 3 displaying acute hemolytic anemia with an infection. While no standard therapy has been established, the condition of the patient in this study improved with conservative treatment, including hydration and antibiotics. CONCLUSION: The mechanisms of hemolysis due to the Rhnull phenotype can vary, but our findings indicate that acute hemolytic crisis caused by the Rhnull syndrome could be associated with infection.